KONDISI TUTUPAN TERUMBU KARANG KIMA DI KAWASAN PERAIRAN DESA BUNATI KECAMATAN ANGSANA KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Jainuddin Jainuddin; Suhaili Asmawi; Abdur Rahman (Fish Scientiae, 2019)
Coral reefs are one of the marine ecosystem which has a very high primary productivity and is a habitat for marine life. This study is to determine the shape and condition of coralreef growth. The method used is the line transect method (Life Form Transect) In this method does not require, but only advised to memorize 27 criteria coral growth expressed as a colony under the line transect, observed and recorded, measured in the scale of centimeters (cm). The results showed that coral reefs are found on the first transect line growth form that is Acropora Branching 2.20%, Acropora tabulate 29.44%, 15.88% Massive and abiotic 7.74%. II found on the transect line growth form that is non-Acropora Branching 4.68%., Massive 49.26%, 18.34% and abiotic. In the transect line III found that Acropora digitate form of growth of 1.80%, 2.10% Non Acropora Branching, Massive abiotic 33.60% and 18.70%. Cover the condition of coral reefs showed that on the first transect lines (medium category) with a percentage of 47.52% coral cover transect line II(both categories) 53.96% and the line transect III (medium category) 37.50%.